Newborn friendly thermometry – Comparative study of body temperature with an infrared versus digital thermometer - Bindu, A; Kutty, P M; Menon, Ashitha; Divya, P; Jose, Soumya (Indian Journal of Child Health, 2015)
Background: Accurate measurement of body temperature is of great importance in day to day neonatology practice. One touch infrared thermometry is safe, accurate, and easy to use. Objective: We aimed at comparing infrared forehead thermometer with an axillary digital thermometer to assess the accuracy. Methods: Axillary and forehead temperatures were measured simultaneously in normal newborn babies using digital and infrared thermometers respectively at a tertiary level teaching hospital in northern Kerala, India and the mean temperature measured by these two methods were compared. Those babies with fever or admitted at Neonatal Intensive Care Unit were not included in the study. Results: Totally, 193 newborns were included in the study with the mean birth weight of 2600±400 g. There was no significant difference in temperature measured by digital and infrared thermometers (97.74±0.91°F vs. 97.81±0.89°F, p=0.44). There was a significant positive correlation between axillary and forehead temperature (r=0.94) and mean difference between two readings was 0.07±0.25°F (p=0.11). Conclusion: Infrared forehead thermometry is as reliable and accurate as axillary digital thermometry. Thus, infrared forehead thermometry can be used in clinical practice, especially in neonatal and postnatal wards where ease of use and speed of obtaining the temperature readings are important.